High rate of centrosome aberrations and correlation with proliferative activity in patients with untreated B-cell chronic lymphocytic leukemia - Hensel, Manfred; Zoz, Martin; Giesecke, Christian; Benner, Axel; Neben, Kai; Jauch, Anna; Stilgenbauer, Stephan; Ho, Anthony Dick; Krämer, Alwin (International journal of cancer, 2007)
B-cell chronic lymphocytic leukemia (CLL) is characterized by a high rate of clonal genomic alterations and a low proliferative activity with cell cycle arrest in G0/G1 phase. Recently, centrosome aberrations have been described as a possible cause of chromosomal instability and aneuploidy in many human malignancies. To investigate whether centrosome aberrations do occur in CLL and whether they correlate with common prognostic factors and disease activity, we examined peripheral blood mononuclear cells (PBMC) from 70 patients with previously untreated CLL using an antibody to γ-tubulin. All 70 CLL samples displayed significantly more cells with centrosome aberrations (median: 26.0%, range 11.0-41.5%) as compared to peripheral blood B lymphocytes from 20 age-matched, healthy individuals (median: 2.0%, range 0-6%; p < 0.001). The extent of centrosome aberrations correlated with the proliferative activity of the CLL cases as measured by lymphocyte doubling time (p = 0.02) as well as with time to first treatment (p = 0.05). Accordingly, more centrosome aberrations were found in PHA-stimulated T lymphocytes from healthy individuals as well as in B cells from surgically removed tonsil tissue of patients with acute tonsillitis as compared to the peripheral blood B lymphocytes from the control group. In contrast, no correlation was observed between centrosome aberrations and immunoglobulin VH gene mutation status or cytogenetically defined risk groups. These findings suggest that, despite the common observation of most CLL cells remaining in G0/G1 phase, their centrosome replication process is deregulated and correlates to the proliferative activity of CLL cells. © 2007 Wiley-Liss, Inc.
Gesehen am 18.10.2021